Some comments on certain statistical aspects of the study of the microbiome. (10th July 2019) - Ferreira, José A; Fuentes, Susana
ABSTRACT: This note complements and clarifies part of the work of Hawinkel et al. recently published in the journal and suggests some more or less standard tools and methods for carrying out association studies of the microbiome.